The Unavailability of Preventive Care for Childrenduring the COVID-19Pandemic and Parental Mental Health - Kien Le (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The outbreak of the coronavirus disease 2019 (COVID-19) causing millions of people to be infected has posed major public health and governance challenges. This study evaluates the extent to which the unavailability of preventive care services for children due to the pandemic affects parentalpsychological wellbeing. We find that parentshaving no access to preventive care servicesfor their children due to the pandemic are 6.55, 5.04, 3.90, and 3.85 percentage points more likely to feel anxious, worried, displeased, and depressed every day. The study calls for the expansion of preventive care services for childrenduring the pandemic, especially for disproportionately affected communities.